Gender Differences in Appropriate Shocks and Mortality among Patients with Primary Prophylactic Implantable Cardioverter-Defibrillators: Systematic Review and Meta-Analysis - Conen, David (PLoS One, 2016)
BACKGROUND: Some but not all prior studies have shown that women receiving a primary prophylactic implantable cardioverter defibrillator (ICD) have a lower risk of death and appropriate shocks than men. PURPOSE: To evaluate the effect of gender on the risk of appropriate shock, all-cause mortality and inappropriate shock in contemporary studies of patients receiving a primary prophylactic ICD. DATA SOURCE: PubMed, LIVIVO, Cochrane CENTRAL between 2010 and 2016. STUDY SELECTION: Studies providing at least 1 gender-specific risk estimate for the outcomes of interest. DATA EXTRACTION: Abstracts were screened independently for potentially eligible studies for inclusion. Thereby each abstract was reviewed by at least two authors. DATA SYNTHESIS: Out of 680 abstracts retained by our search strategy, 20 studies including 46’657 patients had gender-specific information on at least one of the relevant endpoints. Mean age across the individual studies varied between 58 and 69 years. The proportion of women enrolled ranged from 10% to 30%. Across 6 available studies, women had a significantly lower risk of first appropriate shock compared with men (pooled multivariable adjusted hazard ratio 0.62 (95% CI [0.44; 0.88]). Across 14 studies reporting multivariable adjusted gender-specific hazard ratio estimates for all-cause mortality, women had a lower risk of death than men (pooled hazard ratio 0.75 (95% CI [0.66; 0.86]). There was no statistically significant difference for the incidence of first inappropriate shocks (3 studies, pooled hazard ratio 0.99 (95% CI [0.56; 1.73]). LIMITATIONS: Individual patient data were not available for most studies. CONCLUSION: In this large contemporary meta-analysis, women had a significantly lower risk of appropriate shocks and death than men, but a similar risk of inappropriate shocks. These data may help to select patients who benefit from primary prophylactic ICD implantation.